Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/cancers13225736
|View full text |Cite
|
Sign up to set email alerts
|

Can Naloxegol Therapy Improve Quality of Life in Patients with Advanced Cancer?

Abstract: This observational study aims to evaluate the efficacy of naloxegol therapy in resolving opioid-induced constipation (OIC) and in improving the quality of life in a home palliative care cancer setting. Advanced cancer patients with OIC (Rome IV criteria) not relieved by laxatives started a naloxegol therapy 25 mg/day for 4 weeks. Quality of life was evaluated by Patient Assessment of Constipation Quality-of-Life (PAC-QoL) at day 0 and day 28; background pain by Numerical Rating Scale, number of weekly spontane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…While cancer patients have not been included in clinical trials, 37 we observed that about a quarter of the patients in Germany and in the UK and over half of the patients in Sweden and Norway had a history of cancer, in accordance with real‐world data from France 40 and in agreement with the experts from the Delphi consensus who unanimously endorsed PAMORAs as alternative treatments of OIC in patients with cancer 41 . For instance, previous real‐world studies supported the effectiveness and tolerability of naloxegol in patients with advanced cancer 40,42 . Evidence from the large Spanish real‐world study (KYONAL), the first long‐term real‐world study specifically focusing on cancer patients, revealed that 77.8% of individuals with OIC responded favorably to naloxegol treatment at the 12‐month mark 36 .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…While cancer patients have not been included in clinical trials, 37 we observed that about a quarter of the patients in Germany and in the UK and over half of the patients in Sweden and Norway had a history of cancer, in accordance with real‐world data from France 40 and in agreement with the experts from the Delphi consensus who unanimously endorsed PAMORAs as alternative treatments of OIC in patients with cancer 41 . For instance, previous real‐world studies supported the effectiveness and tolerability of naloxegol in patients with advanced cancer 40,42 . Evidence from the large Spanish real‐world study (KYONAL), the first long‐term real‐world study specifically focusing on cancer patients, revealed that 77.8% of individuals with OIC responded favorably to naloxegol treatment at the 12‐month mark 36 .…”
Section: Discussionsupporting
confidence: 85%
“…41 For instance, previous real-world studies supported the effectiveness and tolerability of naloxegol in patients with advanced cancer. 40,42 Evidence from the large Spanish real-world study (KYONAL), the first long-term real-world study specifically focusing on cancer patients, revealed that 77.8% of individuals with OIC responded favorably to naloxegol treatment at the 12-month mark. 36 Further supporting these results, a recent multinational Naloxegol Cancer Study (NACASY), carried out across 26 centers in ten European countries, reinforced the observed improvements in constipation and quality of life in patients dealing with cancer-related pain and OIC and confirmed the established safety profile of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…between treatment groups (C20: 45.5%, C25: 43.3%, D75: 42.7%) % patients with pain progression did not differ sig. between treatment groups (C20: 59.1%, C25: 61.6%; D75: 54.0%,) Febrile neutropenia, neutropenic infection, diarrhoea, haematuria, peripheral neuropathy, stomatitis, peripheral oedema, alopecia, & nail disorders [ 77 ] Patients with mCRPC who had disease progression within 12 mths of receiving either abiraterone or enzalutamide (n = 255) were recruited into clinical trial #NCT02485691; patients were randomized (1:1) to either IV cabazitaxel every 3 wks at 25 mg/m 2 with once-daily prednisone and G-CSF (7 cycles), or the other androgen-signaling-targeted inhibitor (abiraterone 1000 mg plus prednisone daily or enzalutamide 160 mg once-daily) for 4-cycles Secondary Pain progression by BPI-SF or level of WHO cancer pain analgesia used WHO cancer pain analgesic level of 2 to 3 [on a 3-point scale, with higher numbers indicating use of stronger analgesic agents At baseline, 69% of patients had pain progression Pain response was evaluable in 111 patients in cabazitaxel group & 109 patients in androgen-signalling-targeted inhibitor group A confirmed pain response was achieved in 45% of patients in the cabazitaxel group, but only 19.3% in the androgen-signalling-targeted inhibitor group Infection, bronchial aspiration, functional deterioration due to disease progression, spinal cord compression and head injury, pulmonary thromboembolism, cardiac disorder, cerebral bleeding, renal failure and general health deterioration [ 28 ] Patients with mCRPC (n = 150); ProCAID phase 2 trial (NCT02121639) with patients randomly assigned to either oral capivasertib (320 mg twice-daily, 4 days on/3 days off from day 2 each cycle) or matched placebo in combination with IV docetaxel (75 mg/m 2 , day 1 each cycle) & twice-daily prednisone (5 mg) for up to 10 cycles at 3 wk intervals. Study continued until disease progression Secondary Bone pain changes using the BPI No sig.…”
Section: Radiotherapy and Bone-targeting Agents For Relief Of Metasta...mentioning
confidence: 99%
“…However, the number of patients with a pain response was too small to evaluate possible treatment-related differences [ 11 ]. In the FIRSTANA phase 3 trial (NCT01308567), patients who had chemotherapy-naïve mCRPC, were randomized to cabazitaxel at 20 or 25 mg/m 2 (C20 and C25 respectively) or docetaxel at 75 mg/m 2 (D75), plus prednisone once-daily, for a median of 9 treatment cycles [ 77 ]. Overall, the median times to pain progression-free survival, the percentage of patients with a pain response and those with pain progression did not differ significantly between the three treatment arms (Table 3 ) [ 77 ].…”
Section: Radiotherapy and Bone-targeting Agents For Relief Of Metasta...mentioning
confidence: 99%
See 1 more Smart Citation